Research in the history of economic thought and methodology. Vol. 30, pt. 2, - Johnson, Marianne F.; Emmett, Ross B.; Biddle, Jeff (Research in the history of economic thought and methodology., 2012)
This volume includes archival documents and essays exploring the inter-relationship between the government and the economy. In the first piece, Levy, Peart, and Albert examine the one-sided controversy generated by Rose Wilder Lane and V. Orval Watts against a new generation of Keynes-influenced textbooks which focused on governmental policy and the scope of government activity. In addition to their essay, Levy et al. include significant and interesting historical documents as part of the story. The second piece, by Warren J. Samuels, examines Heinrich von Treitschkes view on property as a function of politics using archival documents. The last three pieces include a detailed examination of Warren J. Samuelss views on the economic role of government, based on his course notes in the area. Two sets of notes are published in addition to the introductory essay.